Selected Bibliography “Vocational education and training in European countries" : References generated from the “Literature Database for Vocational Education and Training" (www.ldbb.de) - Linten, Markus [Verfasser]; Prüstel, Sabine [Verfasser]; Woll, Christian [Verfasser] (Bundesinstitut für Berufsbildung, 2014)
This selected bibliography was compiled on the occasion of the 42nd WorldSkills, which took place in Leipzig from 2 to 7 July 2013 and offers an overview of current trends and developments within different vocational education and training (VET) systems in Europe. Germany's dual VET system that combines work-based learning with part-time schooling enjoys an excellent reputation internationally and is in increasing demand. But in general, a growing interest in models of dual VET systems, which can also be found in Austria and Switzerland, can be observed. For this reason, a particular focus of the bibliography lies on the VET systems of Germany, Austria and Switzerland. By choosing only references to literature available in English language, we wish to foster the exchange of ideas and experiences about VET across Europe and to give some new impulses for the further discussions concerning the continuing process of modernizing VET systems. (BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsbildung; Berufsbildungssystem; Berufsbildungspolitik; Berufsbildungsforschung; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Schweiz; Europa